Nilai-Nilai Ethnoparenting Untuk Anak Usia Dini di PAUD Al-Hidayah, Kecamatan Pemenang, Lombok Utara - Astini, Baik Nilawati; Nurhasanah, Nurhasanah; Rachmayani, Ika; Gunawan, Gunawan; Adilah, Safa Cinta (Indonesian Journal of Education and Community Services, 2025)
This study examines the implementation of ethnoparenting socialization at PAUD Al-Hidayah, North Lombok, aimed at evaluating parents’ understanding of the importance of integrating local cultural values into early childhood care. A qualitative descriptive approach was applied through participatory observation, documentation study, and group discussions. Findings indicate that the program successfully enhanced parental awareness of core values such as religiosity, cultural identity, connection with nature, communal cooperation, and the father’s role in child-rearing. These results align with various ethnoparenting studies across Indonesia, including those in Kapuas Hulu, Madura, Sundanese, Minangkabau, and Pamona communities, which emphasize the importance of local wisdom in shaping children’s character. Therefore, ethnoparenting socialization can be considered an effective strategy to strengthen family education in frontier, outermost, and disadvantaged regions.